1993
DOI: 10.1177/106907279300100105
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Meaning of Profile Elevation in the Vocational Preference Inventory

Abstract: Correlates of profile elevation and two differentiation indices in the Vocational Preference Inventory (VPI), Self-Directed Search, and related inventories are examined to clarify the meaning of elevated and low profiles. The traditional differentiation index is not independent of profile elevation. Other results imply that profile elevation is also related to indicators of a tendency to endorse items in the positive direction and to independent measures of positive, energetic, or impulsive response style. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
50
4
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 18 publications
6
50
4
1
Order By: Relevance
“…Gottfredson and Jones (1993) also concluded that profile elevation is only modestly related to external criteria such as involvement, interpersonal competency, identity, or positivity and would therefore be of only marginal practical relevance.…”
Section: Research On Interest Profile Elevationmentioning
confidence: 99%
“…Gottfredson and Jones (1993) also concluded that profile elevation is only modestly related to external criteria such as involvement, interpersonal competency, identity, or positivity and would therefore be of only marginal practical relevance.…”
Section: Research On Interest Profile Elevationmentioning
confidence: 99%
“…A low profile elevation is found to be moderately correlated with depressive traits, unsociability, and a lack of willingness to explore occupations not previously considered (Bullock & Reardon, 2005Fuller et al, 1999). The researchers emphasised that the interpretation of students' vocational interests can be facilitated by using differentiation and profile elevation scores together (Bullock & Reardon, 2005;Gottfredson & Jones, 1993).…”
Section: Profile Elevation and Differentiationmentioning
confidence: 92%
“…Leung, Conoley, Scheel, and Sonnenberg (1992) examined the theorised relationship between vocational identity and differentiation with a sample of 464 academically superior high school students, and found no association between the two constructs. Gottfredson and Jones (1993) correlated differentiation and vocational identity with 250 female and 495 male Navy recruits. Neither of the correlations in the gender groups was significant.…”
Section: Differentiation and Vocational Identitymentioning
confidence: 95%
See 2 more Smart Citations